The effects of television drama on cultural identity for example, the drama Wolves on Kurdmax - Hama, Asst.Prof.Dr. Yohan Osman; Karim, Asst.L. Shaho Khawarham (Sulaimani Journal for Humanities, 2025)
This study aims to identify and analyze the values associated with cultural identity included in the drama series (Wolves) that was shown on the Kurdmax channel. With the identification and analysis of the artistic, media and social values contained in the drama, and also identify the effects of wolves’ drama on cultural identity. To achieve these objectives, the researchers used the descriptive method supported by content analysis with observation to collecting the data, for the purpose of analysis (11) episodes representing (%50) of the total drama that were selected in an organized random manner. Finally, the study concluded that a new and professional work was done in this drama, in terms of techniques (filming, lighting, and accessories). But in terms of the embodiment of cultural values; such as (language, traditions, messages, ethics), it’s at a very weak level. Because the drama depicts Kurdistan as a jungle full of wolves by showing two mafia groups, which the practice all kinds of conflicts, killings, violence and disgusting activities that aren’t common in society, just to obtain the treasure that symbolizes the country's wealth, and smuggle it to Turkey. The study shows that the reflection of cultural identity in this drama is at a very weak level, but rather worked to distort the reality of Kurdish society to a large extent, and some scenes encourage violence, betrayal, fraud, and squandering of public property. The researchers concluded that the artistic works published in the media become part of the media message, so they suggest that the concerned authorities take the necessary measures to not published the production of dramas and television series without reviewing it by linguistic and media experts.
Keywords: Impact; Drama; TV Drama; Identity; Cultural Identity